'Perfectly individualized and constantly visible'? Lateral tightness in a prison holding men convicted of sex offences. Issue 1 (16th July 2020) - Ievins, Alice
Late-modern penal power has been described as 'tight'. Through the increasing use of indeterminate sentences and psychological assessment, and the growing insistence that prisoners engage in self-government, the prison monitors and seeks to change those it holds. This tight and disciplinarian power is often described as contributing to the increasing fragmentation and atomisation of the prisoner community. However, this article, which is based on research conducted in a English medium-security prison for men convicted of sex offences, argues that tightness can operate through the prisoner community, in a process which it terms 'lateral regulation'. It shows that prisoners spend a lot of time observing, categorising and policing their peers, in ways which replicate and often uphold the more formal systems of power. However, the relationship between these two systems of power is complex, and prisoners' collective self-regulation can conflict with and challenge the demands of the penal institution, in a way which reveals some of the weaknesses in the institution's disciplinary gaze, and indicates the normative motivations underlying this regulation.